Doping-Free All PtSe2 Transistor via Thickness-Modulated Phase Transition - Das, Tanmoy; Yang, Eunyeong; Seo, Jae Eun; Kim, Jeong Hyeon; Park, Eunpyo; Kim, Minkyung; Seo, Dongwook; Kwak, Joon Young; Chang, Jiwon (American Chemical Society, 2021)
Achieving a high-quality metal contact on two-dimensional (2D) semiconductors still remains a major challenge due to the strong Fermi level pinning and the absence of an effective doping method. Here, we demonstrate high performance "all-PtSe2" field-effect transistors (FETs) completely free from those issues, enabled by the vertical integration of a metallic thick PtSe2 source/drain onto the semiconducting ultrathin PtSe2 channel. Owing to its inherent thickness-dependent semiconductor-to-metal phase transition, the transferred metallic PtSe2 transforms the underlying semiconducting PtSe2 into metal at the junction. Therefore, a fully metallized source/drain and semiconducting channel could be realized within the same PtSe2 platform. The ultrathin PtSe2 FETs with PtSe2 vdW contact exhibits excellent gate tunability, superior mobility, and high ON current accompanied by one order lower contact resistance compared to conventional Ti/Au contact FETs. Our work provides a new device paradigm with a low resistance PtSe2 vdW contact which can overcome a fundamental bottleneck in 2D nanoelectronics.
Keywords: FIELD-EFFECT TRANSISTORS; MOS2; PERFORMANCE; CONTACTS; NANOSHEETS; GRAPHENE